A study on style in Malaysian contemporary printmaking in the national art gallery collection (from 1970's to 1990's) / Mohd Adzman Omar. - Omar, Mohd Adzman (2009)
Throughout these few past decades printmaking in Malaysia has gone through a lot of growth as well as changes in techniques, idea and ways of producing printed artworks. Though considered as an additional media by some artists in this country, printmaking is still a contributor towards the development of visual arts in Malaysia. In this thesis the researcher strives to study and analyze on the styles of the contemporary printmaking in Malaysia from the 1970s to the 1990s. The objectives of this research are to study the development of styles in Malaysian contemporary printmaking; to analyze and determine the factors that influence Malaysian printmakers; and to produce classification of style in Malaysian contemporary printmaking. The research methodology used is qualitative. Twelve printmakers were selected and interviewed to get their personal statements and interpretations of their artworks. The researcher used Feldman method of criticism that comprises four strategies of criticism: description, analysis, interpretation and evaluation to criticize and appreciate the artworks. The researcher analyzed the data based on the theory of style used by art historian, Paul Zucker in order to determine the styles used. The findings of the research showed that most of Malaysian printmakers have been strongly influenced by the National Cultural Congress, and this can be seen in most of their works produced within these three decades. Most of the ideas and images are based on the spiritual movement that emphasizes on religious as well as cultural factors prompted by the congress. Education is also an important factor in the development of style in Malaysian prints, where all selected artists had received formal education from different countries or different school of arts, locally and internationally. Meanwhile, social and political system are not considered as the main factor in the development of style in Malaysia as this country is a free and sovereign one where artists could produce art freely, by using any types of printmaking, images or subject matters. As a conclusion, this research shows that culture and education are the main factors that influenced the development of style in Malaysian Printmaking from the 70s to the 90s.